Karakteristik Faktor Risiko Penderita Katarak - Ade Utia Detty; Ika Artini; Vikko Rachmat Yulian (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
introduction; cataract is one of the causes of blindness in Indonesia and the world. This study aims to determine the characteristics of cataract risk factors. Methodology: This research is a quantitative study with a descriptive design. Samples of 83 people were obtained through Simple Random Sampling and data collection using medical record data. Results: showed that there were 63 cataract patients at the age> 50 years (75.9%). The majority of cataract sufferers were female as many as 48 people (57.8%). The majority of cataract patients without diabetes mellitus were 64 people (75.9%). The majority of cataract patients had a history of hypertension as many as 45 people (54.2%). The majority of cataract patients did not have a history of trauma as many as 73 people (88%). Conclusion: that age, gender, diabetes mellitus status, blood pressure, and eye trauma status are some of the risk factors for cataracts is cataract sufferers